The Radio The World Tunes In - Mattern, Joanne; Nang Chan Yeema (New York, United State The Rosen Publishing Group, Inc., 2003)
Presents information on radio, including its invention, history, how it works, and how it has affected people's lives
Keywords: Juvenile Nonfiction